2022
DOI: 10.1021/acsapm.2c00514
|View full text |Cite
|
Sign up to set email alerts
|

Colorimetric pH-Responsive Biomaterials Based on Pyranoflavylium-Biopolymer Hybrid Conjugates

Abstract: The conjugation of functional molecules into marine-origin biopolymers has been extensively used toward the creation of new (bio)­materials for applications in food and biomedical areas. Herein, two chitosan (CHT) and alginate (ALG) biobased conjugates functionalized with pH-dyes were successfully developed to be integrated as smart labels and tags in biocompatible packaging materials for food spoilage sensing. For that, two pyranoflavylium-based pH-indicator dyes, Pyflav (4) and Pyflav (5), were designed, syn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 57 publications
0
2
0
Order By: Relevance
“…The presence of an extra pyranic ring at the flavylium core, blocking the C-4 position, prevents the hydration reaction for the formation of colorless hemiketal species, thus avoiding tautomerization and isomerization reactions. , Therefore, this type of dye undergoes only acid–base reactions, shifting from the yellow-orange acidic flavylium cation species to pink-blue neutral and anionic quinoidal base species. In a recent work, the design of one appropriate pyranoflavylium (Pyflav) dye and its noncovalent immobilization in an optimized cellulose acetate-based formulation was revealed to be crucial for achieving significant pH-dependent color variation without compromising stability . On the other hand, it was also demonstrated that Pyflav dyes could be chemically grafted onto marine-origin polysaccharides (alginate, chitosan) using carbodiimide coupling chemistry, offering a valuable strategy for developing pH-responsive bioconjugates. In this work, the well-known and efficient “click chemistry” was considered instead to covalently attach a pyranoflavylium-based dye onto a chitosan derivative . Therefore, an azide-containing Pyflav dye (PyFlav-N 3 ) was first designed and synthesized and further functionalized to an alkyne-modified chitosan (CHT-Alk) via copper-catalyzed azide–alkyne cycloaddition reaction (CuAAC).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The presence of an extra pyranic ring at the flavylium core, blocking the C-4 position, prevents the hydration reaction for the formation of colorless hemiketal species, thus avoiding tautomerization and isomerization reactions. , Therefore, this type of dye undergoes only acid–base reactions, shifting from the yellow-orange acidic flavylium cation species to pink-blue neutral and anionic quinoidal base species. In a recent work, the design of one appropriate pyranoflavylium (Pyflav) dye and its noncovalent immobilization in an optimized cellulose acetate-based formulation was revealed to be crucial for achieving significant pH-dependent color variation without compromising stability . On the other hand, it was also demonstrated that Pyflav dyes could be chemically grafted onto marine-origin polysaccharides (alginate, chitosan) using carbodiimide coupling chemistry, offering a valuable strategy for developing pH-responsive bioconjugates. In this work, the well-known and efficient “click chemistry” was considered instead to covalently attach a pyranoflavylium-based dye onto a chitosan derivative . Therefore, an azide-containing Pyflav dye (PyFlav-N 3 ) was first designed and synthesized and further functionalized to an alkyne-modified chitosan (CHT-Alk) via copper-catalyzed azide–alkyne cycloaddition reaction (CuAAC).…”
Section: Introductionmentioning
confidence: 99%
“… 22 On the other hand, it was also demonstrated that Pyflav dyes could be chemically grafted onto marine-origin polysaccharides (alginate, chitosan) using carbodiimide coupling chemistry, offering a valuable strategy for developing pH-responsive bioconjugates. 23 25 In this work, the well-known and efficient “click chemistry” was considered instead to covalently attach a pyranoflavylium-based dye onto a chitosan derivative. 26 Therefore, an azide-containing Pyflav dye (PyFlav-N 3 ) was first designed and synthesized and further functionalized to an alkyne-modified chitosan (CHT-Alk) via copper-catalyzed azide–alkyne cycloaddition reaction (CuAAC).…”
Section: Introductionmentioning
confidence: 99%